Rescue therapy after failed thrombectomy in medium/distal vessel occlusions: A retrospective analysis of an international, multi-center registry - Anastasiou, Aikaterini; Brehm, Alex; Dobrocky, Tomas; Mujanovic, Adnan; de Dios Lascuevas; Marta; Carmona Fuentes, Tomas; López-Frías López-Jurado, Alfonso; Hidalgo Valverde, Blanca; Berlis, Ansgar; Maurer, Christoph J.; Nguyen, Thanh N; et al. (SAGE Publications, 2025)
Background:
There are limited therapeutic options in cases of failed reperfusion (modified thrombolysis in cerebral infarction [mTICI] score < 2b) after stent-retriever and/or aspiration based endovascular treatment (EVT) for acute ischemic stroke. Despite the absence of data supporting its use, rescue therapy (balloon angioplasty and/or stent implantation) is often utilized in such cases. Studies are limited to large vessel occlusions, while the outcomes and complications after rescue therapy in medium/distal vessel occlusions (MDVOs) have not been reported. This study aims to report the outcomes of rescue therapy in MDVO stroke patients.
Methods:
We performed an analysis of the “Blood pressure and Antiplatelet medication management after reScue angioplasty after failed Endovascular treatment in Large and distal vessel occlusions with probable IntraCranial Atherosclerotic Disease” (BASEL ICAD) retrospective registry. All MDVO stroke patients were included in the analysis.
Results:
Out of the 718 registry patients, 87 (12.1%) presented with an MDVO. Fifty-six patients (64.4%) showed an occlusion of the M2 segment of the middle cerebral artery. Rescue stenting was performed in 78 patients (89.7%) while balloon angioplasty alone was performed in 9 patients (10.3%). Successful reperfusion (mTICI score ⩾ 2b) was achieved in 73 (83.9%) patients after rescue therapy. Symptomatic intracranial hemorrhage (sICH) occurred in 8 patients (9.2%) and post-treatment stent occlusion in 12 patients (13.8%). Ninety days mortality was 20.7%. Twenty-eight patients (32.2%) achieved functional independence at 90 days (modified Rankin Scale 0–2).
Conclusion:
Rescue therapy with stenting and/or balloon angioplasty in patients undergoing EVT for isolated MDVO with suspected underlying intracranial atherosclerotic disease is an effective reperfusion strategy but is associated with complications and poor functional outcomes.